PERSEPSI MASYARAKAT TERHADAP KUALITAS PELAYANAN PUBLIK PADA KANTOR PEMERINTAH DAERAH (Studi Pada Kantor Badan Penanaman Modal dan PelayananTerpadu Satu Pintu Kota Padang) - Willy Nofranita, Herlinda Dasril (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
In the implementation of good governance government government as the organizer ofnational and state are required to meet the interests and needs of its people. Increased publicawareness of the quality of public services, demanding the government as public serviceproviders to improve the quality of service. This study aims to look at the perception of thepublic as users of public services to the quality of public services received, and the constraintsfaced by public service providers in providing services to users of public services. This studyis a qualitative research where the primary data obtained from participants of the questionnaireanswers provided about the truth is real, followed by observation. The analytical methods usedare Level Outcomes average of answers to participants as a service user to know the user'sperception of the quality of public services received and interviews with public serviceproviders. The survey results revealed that the public perception of the quality of publicservices in the Office of the Board of Investment and Integrated Services One Stop KotaPadang is good. perceived constraints of service personnel is the quantity of human resourcesinsufficient by the number of permit applications submitted, the building and the room theofficers were less worthy, narrow parking for shared use with other offices. SOPs aresometimes not enforced, the understanding of different societies, socialization has been done,but not yet effective because of limited personnel and budget.Keyword : User’s Percepcion, Public Services